Imagining What Could Have Happened: Types and Vividness of Counterfactual Thoughts and the Relationship With Post-traumatic Stress Reactions - Blix, Ines; Kanten, Alf Børre; Birkeland, Marianne Skogbrott; Thoresen, Siri (Frontiers in Psychology, 2018)
A growing body of research suggests that counterfactual thinking after traumatic events is associated with posttraumatic stress reactions. In this study we explored frequency of upward and downward counterfactuals in trauma-exposed individuals, and how trauma-related counterfactuals were represented in terms of vividness. We examined the relationships between vividness and frequency of counterfactual thoughts and posttraumatic stress reactions in two groups who had experienced different types of traumatic exposure, namely survivors and bereaved from the fire on the ferry Scandinavian Star in 1990. Even after 26 years, both survivors and bereaved reported that they currently entertained thoughts about what could have happened during the fire on Scandinavian Star. Survivors reported more downward counterfactuals than the bereaved, whereas the bereaved reported more upward counterfactuals than the survivors did. Vividness of counterfactual thoughts, as well as reported frequency of upward and downward counterfactuals, were associated with posttraumatic stress reactions. Our results suggest that both upward and downward counterfactuals can be harmful, and that vivid counterfactuals about a traumatic event might play a similar role in posttraumatic stress as trauma memories. Therefore, traumatized individuals who entertain counterfactual thoughts may benefit from interventions that target these thoughts specifically.